(untitled) (Sir Salimullah Medical College Journal, 2022)
Immature ovarian teratomas are uncommon germ cell tumors of unknown etiology. Preoperative diagnosis can be difficult impacting the management of this case. Color Doppler ultrasound can predict malignant nature as well as exclude complications earlier, which is important for management & prognosis. Here we present a young female patient came for an emergency ultrasound with progressive abdominal distension and pain. Ultrasound showed huge ascites with a large, irregular, heterogeneous, predominantly solid, left ovarian mass with internal calcifications, focal echogenic & anechoic areas and prominent intratumoral arteries with low resistant flow (RI: 0.34). The lesion was further evaluated on a CT later showing heterogeneous contrast enhancement, fat-fluid densities & calcifications. Sir Salimullah Med Coll J 2022; 30: 89-92